Upconversion nanocrystal 'armoured' silica fibres with superior photoluminescence for miRNA detection. Issue 49 (4th June 2018) - Wang, Gang; Fu, Yike; Ren, Zhaohui; Huang, Jie; Best, Serena; Li, Xiang; Han, Gaorong
Abstract : A FRET biosensor, based on silica nanofibres armoured with NaYF4 :Yb, Er upcoversion nanoparticles (SiO2 @UCNP), offers a simple and quantitative methodology for cancer biomarker (miRNA-21) detection. Abstract : We have fabricated a flexible membrane, consisting of SiO2 nanofibres armoured with upconversion nanoparticles, exhibiting intense photoluminescence. These assemblies were subsequently grafted with molecular beacons to produce a biosensor suitable for the detection of specific microRNA and with applications in early cancer detection and point-of-care diagnosis.